PARTISIPASI POLITIK MASYARAKAT MISKIN KOTA DALAM PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN 2014 DI KOTA MAKASSAR - Andi Nur Amaliah; Muhajirah Hasanuddin; Alimuddin Said (Otoritas : Jurnal Ilmu Pemerintahan, 2015)
This research for knowing the political participation of the urban poor and the factors that affect the political participation of the urban poor in the election of President and Vice President in 2014 in the Village Mangasa Subdistrict Tamalate Makassar. The kind of research is descriptive quantitative research by explaining the political participation of the urban poor, the sample of 30 people in the poor communities selected by purposive sampling. The results showed a participation rate of urban poor in the election of president and vice president in 2014 in the Village Mangasa Tamalate District Makassar. The form of political participation of the poor consists of electoral activities, the lobby, the organization's activities, find connections and acts of violence, political participation Reasons divided on the influence of community groups, availability of facilities, and low motivation. Typology of political participation consists of poor and semi apathetic apathy. As well as political communication is divided into function information and education functions. The political participation of the urban poor is also strongly influenced by factors supporting consisting of Consciousness or the will and the influence of the government, as well as inhibiting factors are factors Environmental and Economic factors. Tujuan penelitian ini untuk mengetahui partisipasi politik masyarakat miskin kota dan faktor-faktor yang mempengaruhi partisipasi politik masyarakat miskin kota dalam pemilihan Presiden dan Wakil Presiden 2014 di Kelurahan Mangasa Kecamatan Tamalate Kota Makassar. Jenis penelitian adalah deskriptif kuantitatif dengan menggunakan sampelnya sebanyak 30 orang masyarakat miskin yang di pilih secara Purposive Sampling. Hasil penelitian menunjukkan tingkat partisipasi politik masyarakat miskin kota dalam pemilihan presiden dan wakil presiden 2014 di Kelurahan Mangasa Kecamatan Tamalate Kota Makassar. Adapun bentuk partisipasi politik masyarakat miskin terdiri dari kegiatan pemilihan, lobby, kegiatan organisasi, mencari koneksi dan tindakan kekerasan, Alasan partisipasi politik terbagi atas pengaruh kelompok masyarakat, ketersediaan sarana, dan rendahnya motivasi. Tipologi partisipasi politik terdiri dari masyarakat miskin apatis dan semi apatis. Serta komunikasi politik terbagi atas fungsi informasi dan fungsi pendidikan. Partisipasi politik masyarakat miskin kota juga sangat dipengaruhi oleh faktor pendukung yang terdiri dari Kesadaran atau kemauan dan pengaruh pemerintah, serta faktor penghambat yaitu faktor Lingkungan dan faktor Ekonomi.